PELATIHAN PEMBUATAN WEBSITE SENDIRI BAGI APARAT DESA RULUNG HELOK KECAMATAN NATAR LAMPUNG SELATAN - Erna Cucu Rahayu; Teuku Muhammad Fawaati (UNIVERSITAS MITRA INDONESIA, 2022)
Rulung Helok Village is one of 26 villages in Natar District, South Lampung Regency. This village is estimated to have been formed since the 1700s, this is because this village has 12 generations according to local stories. Led by a traditional Lampung leader with the title TuanPower. It was only after the independence period that this village was formed in the 1900s. Most of the villagers earn their income from agriculture, plantations, and livestock (duck). The rest of the population generates income from family businesses such as making clothes (tailors), public transportation businesses, ready-to-drink water (ASM), and basic food stalls. Keywords—3-5 Boarding School, Human Resource, Learning